Despite citizenship. Autonomie migranti e diritto alla città L’occupazione dell'Ex-Moi a Torino - Stopani, Antonio (2018)
This article explores how subaltern migrants who are subject to daily securitarian technologies and policies produce social spaces and plots in order to make their mobility autonomous. The ethnographic research conducted in the Ex Moi buildings in Turin - occupied since 2003 by several hundred migrants - examines the set of actions that support their local presence outside of the humanitarian and emergency system. Despite citizenship studies the Ex Moi Squat as an infrastructural support - both material and immaterial - that allows the material deployment of relational processes with and within the city and the pursuit of a set of rights which, although detached from citizenship, are finalized to ensure residence, work, information and support otherwise denied.